Comparative features in Islamic architecture - al-Maliki, Kabila Fares (Iraqi Journal of Architecture and Planning, 2009)
Most ofthe recent architectural studies directed towered the necessity of using the architectural characterization of the cultural inhlrited ofthe Islamic Architecturi in the futurist designs, in away that unified the contemporary architecture with the historical roots. The contemporary architecture environment ofthe types and styles various in functions, forms and goals pushing on limitation of copying these types of traditional architectural elements , but trying to study and realize the cognitional meanings and using architectural solutions that had specific characterizations which connected with the theoretical believes which came from the cultural environment ofthe Islamic community in the contemporary designs. For that need ,for the designers to use the character of the Islamic Architecture in the contemporary designs depending on architectural studies searching in these meanings which must be objectively and comprehensively for (architectural studies and researches) and (practical topics in the contemporary architecture). Monumentality is one of these meanings, which is related to the cultural environment that needs an objectively comprehensive study. The absence of the cognitional frame was the main problem ol the research that is related to the monumentality in the Islamic Architecture. For that the main target ofthe research was to put the cognitional frame ofthe Monumentality in Architecture so it can judge any type or style in architecture including Islamic Architecture. The research studied three tlpes of architecture (Babylon, Roman and Gothic) focussing basically and intensively on its Monumentality in its architecture to give the cognitional frame of the Monumentalitv in ils meaning , intentions , goals and its topics in architecture, so it can judge any architecture including Islamic Architecture which had special characteristic that are specialized the Monumentality in Islamic Architecture in comparison with other Architectures.